Respostas morfológicas e fisiológicas do amendoim, gergelim e mamona a ciclos de deficiência hídrica. - Pinto, Ciro de Miranda (2006)
A greenhouse research was carried out at the Universidade Federal do Ceará, Campus do Pici, from January to March 2006, with the objectives of studying the response of castorbean (Ricinus communis L.), sesame (Sesamum indicum L.) and peanut (Arachis hypogaea L.) to cycles of water deficit in the early vegetative growth phase. The following cultivars for each crop were evaluated: peanut cultivars PI 165317 (group Spanish) and 57422 (group Virginia); sesame CNPA G3 and CNPA G4; and castorbean Mirante and BRS 149 Nordestina. The seeds were planted in PVC tubes 100 cm log and 10 cm wide, filled with sand soil. The cultivars received two water regime treatments: daily irrigation and cycles of water stress. Several variables were determined relative to plant water status, gas exchange, top and root growth and root system distribution in the soil profile. Plant harvest was accomplished at 50, 55 and 56 days after planting for sesame, peanut and castorbean, respectively. The variables water potential, relative water content, leaf transpiration, leaf photosynthesis and stomatal conductance were reduced in all three crops in response to water stress. The relation between leaf and ambient temperature increased in response to water stress. The water use efficiency was not affected by the stress imposed in castorbean and peanut. On the other hand, in sesame this variable decreased in response to water stress. Tops, roots and total dry matter as well as the root system volume were reduced in all species in response to water stress. Root shoot ratio increased in response to water stress for sesame and peanut, while for castorbean this relation remained unchanged. Among the crops studied, peanut plants had the smallest dry matter partition to the roots; sesame stayed in an intermediary position and castorbean partitioned the higher proportion of dry matter to roots. Peanut showed a large modification in the root system stratification in response to the water stress, with the increase of proportion of the root system in the deep soil. Castorbean showed the smaller response as far as deepening of the root system and sesame retained an intermediary position. All three crops, no matter the water regime was, had the most proportion of the root system in the first 25 cm layer of soil. The leaf number and leaf area were reduced in the three species in response to water stress.